Sex education, health & moral education for students in Winong Pati, Central Java Schools - Sholihah, Hidayatus; Zaenurrosyid, A. (Universitas Sarjanawiyata Tamansiswa, 2025)
This dedication explores the importance of sex education, health, and moral education for santri-students in Winong Schools, Pati, Central Java. Sex education, health, and moral education play a vital role in shaping the physical, mental, and mental development of students. This devotion has important implications for improving students' understanding of sex, health, and moral values. The recommendations derived from this study can be a guide for schools, governments, and families to improve sex education, health, and moral education among santri- students at Pati Schools, Central Java. Thus, it is expected that the younger generation will become individuals more aware of health and moral behavior, as well as able to make wise decisions in their lives. This dedication uses interesting training methods, which means that the trainer delivers information and examples to the participants of the activity. The results of dedication show that most students at Winong Pati Schools do not have adequate knowledge of sex, reproductive health, and moral education. This lack of understanding can lead to risky behaviour, such as unsafe sex, drug abuse, and asylum. The results also show that the implementation of sex education, health, and moral education in pesantren schools in Winong Pati district is still limited. Further efforts are needed to integrate these materials into the educational curriculum, as well as training teachers so that they can provide accurate and accurate information to students.